THE ROLE OF MOBILE SMS-REMINDERS IN IMPROVING DRUGS COMPLIANCE IN PATIENTS RECEIVING ANTI-TB TREATMENT FROM DOTS PROGRAM - Farooqi, Rukhsana Javed; Ashraf, Sadia; Zaman, Mukhtiar (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the role of mobile SMS-reminders in improving drugs compliance in patients receiving anti-TB treatment from DOTS program. Methodology: This randomized controlled trial was conducted from June 2014 to June 2015, in two centres: Khyber Teaching Hospital Peshawar and Emergency Satellite Hospital Nahaqi. Patients enrolled for anti-TB drugs were distributed in intervention and control groups; daily mobile SMS reminders were sent to patients of intervention group on top of usual DOTS. Patients were followed on monthly basis. Primary outcome measure was default, defined as not taking medicine for two consecutive months. Results: Total of 148 patients were enrolled, 74 in each group. Baseline characteristics of both groups were comparable. Mean age was 29.4 ±17.6 years, with 63 (42.6%) males, 65 (43.9%) smear-positive TB, 24 (16.2%) smear-negative TB, and 59 (39.9%) extra-pulmonary TB. Treatment-default was found in 7 (4.7%) patients, out of these 3 patients (4.1%) were in "intervention group" and 4 patients (5.4%) were in "control group", both groups were comparable with no significant statistical difference (p = 0.983). Conclusion: Number of treatment-default cases was lower in "intervention group" than "control group", but this numerical difference was not significant statistically.